Multilayered control of chromosome replication in Caulobacter crescentus. (9th January 2019) - Frandi, Antonio; Collier, Justine
Abstract : The environmental Alphaproteobacterium Caulobacter crescentus is a classical model to study the regulation of the bacterial cell cycle. It divides asymmetrically, giving a stalked cell that immediately enters S phase and a swarmer cell that stays in the G1 phase until it differentiates into a stalked cell. Its genome consists in a single circular chromosome whose replication is tightly regulated so that it happens only in stalked cells and only once per cell cycle. Imbalances in chromosomal copy numbers are the most often highly deleterious, if not lethal. This review highlights recent discoveries on pathways that control chromosome replication when Caulobacter is exposed to optimal or less optimal growth conditions. Most of these pathways target two proteins that bind directly onto the chromosomal origin: the highly conserved DnaA initiator of DNA replication and the CtrA response regulator that is found in most Alphaproteobacteria . The concerted inactivation and proteolysis of CtrA during the swarmer-to-stalked cell transition license cells to enter S phase, while a replisome-associated Regulated Inactivation and proteolysis of DnaA (RIDA) process ensures that initiation starts only once per cell cycle. When Caulobacter is stressed, it turns on control systems that delay the G1-to-S phase transition or the elongation of DNA replication, most probably increasing its fitness and adaptation capacities.